Pengaruh Data Warehouse Terhadap Pengambilan Keputusan - Imanda, Resda Atsila; Suroso, Sugeng; Fauzi, Achmad; Simanjuntak, Henny Feronika; Azizah, Zakiyyatul; Destianty, Alena; Mutmainnah, Audy Zalfa; Shaffa, Ghaitza Zarka Zahira (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
The method used in this article is a quantitative method, so that it can be seen how the data warehouse affects decision making. This article will discuss more deeply the effect of the data warehouse on decision making. A data warehouse is a place where all historical data from an organisation or company is stored in detail. A data warehouse can influence the decision-making process of an organisation or company by presenting data that has been collected and then processed into useful information. In addition, with a data warehouse, information can be accessed quickly, accurately, and more efficiently. Information systems also affect the decision-making process by providing data that will be processed and produce alternative solutions. The purpose of preparing this article is for further research material to make hypotheses that have an impact on one variable or another. The results of the discussion of this article are: (1) Data Warehouse affects Decision Making; (2) Information Systems affect Decision Making; (3) Data Warehouse plays a role in Decision Making.